2015
DOI: 10.1589/jpts.27.2293
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of short-term structured exercise in non-overweight women with polycystic ovary syndrome: a prospective randomized controlled study

Abstract: [Purpose] The short-term effects of structured exercise on the anthropometric, cardiovascular, and metabolic parameters of non-overweight women diagnosed with polycystic ovary syndrome were evaluated. [Subjects and Methods] Thirty women with a diagnosis of polycystic ovary syndrome were prospectively randomized to either a control group (n=16) or a training group (n=14) for a period of 8 weeks. Anthropometric, cardiovascular, and metabolic parameters and hormone levels were measured and compared before and aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 31 publications
(30 reference statements)
2
59
0
1
Order By: Relevance
“…Twelve trials compared exercise to usual care or minimal intervention [32, 34, 97, 102, 104, 108111, 117119]. Three trials each compared combined exercise and diet with diet only [33, 98, [105]], and exercise and diet combined with usual care [99, 100, 107].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve trials compared exercise to usual care or minimal intervention [32, 34, 97, 102, 104, 108111, 117119]. Three trials each compared combined exercise and diet with diet only [33, 98, [105]], and exercise and diet combined with usual care [99, 100, 107].…”
Section: Resultsmentioning
confidence: 99%
“…Eight trials (44%) did not report any attrition [98, 99, 102, 104, 107, 109, 110, 118]. Where reported, attrition ranged from 6% [117] to 50% [33] with a median value of 19.5%; five trials (28%) reported attrition over 20% [32, 33, 97, 100, 105]. Reasons for exercise dropouts included non-exercise related injury [3234, 97, 119], pregnancy [3234, 100, 119], time [33, 34, 97], work/family commitments [32, 33, 119], personal reasons [33, 105, 108, 111], medical grounds [97, 105, 111], and relocation [33].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, there is limited research available to give women with PCOS sufficient recommendations on physical activity and exercise. Some studies have demonstrated positive effects in reproductive outcomes after exercise, with concomitant improvements in insulin sensitivity and/or visceral fat 20–24. However, more knowledge is needed about the underlying mechanisms for improvement in fertility after exercise training, as discussed in several systematic reviews on lifestyle interventions and fertility 12 25 53 54.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise training positively affects metabolic, cardiovascular and psychological outcomes in women with PCOS, but the effect on fertility is unclear 4 12 17–19. Some trials20–24 and systematic reviews12 25 report improved ovulation or menstruation frequency after a period of exercise training or after a combined exercise-diet intervention 26. Two of these studies indicate a weight-independent effect of exercise on fertility, suggesting insulin sensitivity to be a key factor 21 23.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation